The demographic challenges of development in Africa - (:unkn) unknown (My University, 2023)
For centuries, Africa has remained a sparsely populated continent, with the exception of the settlement of the Nile Valley. As the mortality rate fell, and thus as it advanced through the first stage of the demographic transition, especially from the second half of the 20th century onwards, its population growth became higher than the world average, giving Africa a considerably greater absolute and relative weight in the world population, i.e. nearly 18% in 2022, a percentage projected to reach 25% by 2050. Such a development, which must first be measured, raises questions about the demographic challenges of African development.
Keywords: African Research